IPVAW male perpetrators convicted in Spain: a typology and characterization based on latent class analysis - Osa-Subtil, Iria de la; Astray, Andrés Arias; Mateo Fernandez, Pedro V.; de Dios-Duarte, María J. (Frontiers in Psychology, 2024)
Men who assault their partners present deficits in the social skills necessary for adequate interpersonal interaction. Not all of them have the same difficulties, thus they do not constitute a homogeneous group. Various studies have proposed different typologies of abusers based on their sociodemographic characteristics, criminal history, intensity and extent of violent or psychopathological traits. The majority of these investigations have been conducted in community samples, prompting the question of their validity in samples of men convicted of gender violence.The aim of this study was to establish a typology of men convicted in Spain for a gender violences crimes. A total of 365 men participated and were subdivided into three classes of abusers based on their childhood, family experiences with violence, criminal history, sexist attitudes and attitudes towards violence, intensity and type of violence, psychopathological state and attachment style.Coinciding with the results found in other research, 30% of the participants were classified as generally violent. They engaged in severe forms of physical, psychological and sexual violence and were more likely to do so than the rest. Additionally, they are more likely to present psychopathological problems and an antisocial character. Twenty-one percent were classified as dysphoric/borderline. They are characterised by minor forms of psychological violence, borderline or depressive symptomatology and an anxious attachment style. The remaining 49% were classified as familial or normalised abusers. This group exhibits moderate attitudes towards violence and sexism, resulting in less psychological and physical aggression. They do not present psychopathological problems and are likely to present a secure attachment style. It is argued that determining the psychological characteristics of each type of abuser would contribute to improving and adapting intervention protocols in Spain, leading to a significant improvement in the current issue of abuse.